Adolescent fathers' experiences in Indonesia: a qualitative study. Issue 1 (1st January 2021) - Astuti, Andari Wuri; Hirst, Janet; Bharj, Kuldip Kaur
ABSTRACT: Adolescent fatherhood is often unplanned and such situations increase adolescents' vulnerability over their life course. The aim of this study was to gain an in-depth understanding of the world as seen through the eyes of Indonesian adolescent fathers who experienced an unplanned pre-marital pregnancy. Sixteen, in person one-to-one interviews were conducted with eight Indonesian adolescent male participants (age 18–19). Interviews were audio recorded, transcribed, translated and thematically analysed. Adolescent's uncharted journeys prevailed as the overarching theme, as they narrated how their life course had impacted on them. They experienced emotional distress, they were controlled by strong social and cultural expectations and nurtured by older family members. Resourcefulness emerged as ways of coping through renewed faith and hope for a better future. The enduring impact of their distress on economic opportunities, marital harmony, social integration, faith and happiness is worthy of further enquiry.